Feynman integrals: Synergies between particle physics and gravitational waves - Mandal Manoj Kumar (EPJ Web of Conferences)
Feynman integrals are essential for computing scattering amplitudes. Linear relations among these integrals, through Integral-By-Parts (IBP) identities, reduce them to a smaller set of independent integrals, known as master integrals (MIs). In twisted de-Rham cohomology, Feynman integrals form a vector space with an inner product, called the intersection number, which simplifies this reduction process. These methods have been applied in particle physics and recently extended to gravitational wave physics, notably in modeling binary black hole mergers. This proceedings highlights the synergy between these fields, showcasing how advanced techniques from Feynman integrals enable high-precision results in both areas.